Blood Glucose Control Strategy for Type 2 Diabetes Patients With COVID-19 - Futatsugi, Hiroyuki; Iwabu, Masato; Okada-Iwabu, Miki; Okamoto, Koh; Amano, Yosuke; Morizaki, Yutaka; Kadowaki, Takashi; Yamauchi, Toshimasa (Frontiers in Cardiovascular Medicine, 2020)
Since December 2019, coronavirus disease 2019 (COVID-19) caused by a novel coronavirus has spread all over the world affecting tens of millions of people. Another pandemic affecting the modern world, type 2 diabetes mellitus is among the major risk factors for mortality from COVID-19. Current evidence, while limited, suggests that proper blood glucose control may help prevent exacerbation of COVID-19 even in patients with type 2 diabetes mellitus. Under current circumstances where the magic bullet for the disease remains unavailable, it appears that the role of blood glucose control cannot be stressed too much. In this review the profile of each anti-diabetic agent is discussed in relation to COVID-19.